An intelligent dental robot. (18th June 2018) - Ren, Limin; Yang, Jiaqi; Tan, Yisong; Hu, Jiale; Liu, Di; Zhu, Jianhua
ABSTRACT: An intelligent dental robot (IDR) is reported for the purpose of artificial denture verification and test. Methods : The IDR is composed of power system, intelligent control and driving system, sensor system and supporting system. Five Maxon motors are adopted to provide the driving force for the IDR. Novel motor linear actuators are developed to mimic the movement of human's masticatory muscles. Forward and inverse kinematics of the IDR are analyzed. Seven high-precision pressure sensors are utilized to detect the force on individual artificial tooth. Results : Motion and force experiments are conducted on the IDR. The maximum biting force provided by the IDR is 490 N. Hysteresis rate of the biting force loading and unloading is less than 3%. The largest displacement for the mandible movement test is found to be 60, 9 and 22 mm in the vertical, protrusive and lateral directions, respectively. Conclusion : IDR can complete simulated human masticatory movement and provide sufficient biting force. Significance : The IDR provides clinical guidance for the design and performance test of artificial denture. GRAPHICAL ABSTRACT: Brief Abstract This paper proposes an intelligent dental robot. The dental robot is to simulate the human's mandible movement and the experiment curves meet the Posselt envelope. The maximum biting force provided by the dental robot is 490 N, which satisfies the human biting force limit.